Optimization Research into the Ultrasonic-assisted Extraction to Separate Polyphenol from Green Tea Waste - Lan Huong Phung; Trung Kien Tran; The Cuong Nguyen; Hong Quang Do; Thu Tra Phan; Hong Son Vu; Tien Huy Nguyen (ASEAN Journal of Chemical Engineering, 2012)
Today, green tea leaves (Camellia sinensis) have been grown in nearly 30 provinces in Vietnam. Catechins, which are polyphenols, are abundant in green tea. In a freshly picked tea leaf, polyphenols can compose up to 30% of the dry weight. Recently, researchs have focused on tea polyphenols due to its potent anti-oxidant activity, anti-inflammatory and anti-cancer effects. Viet Nam currently ranks the fifth in the world in tea production and export turn-over. However, green tea is made from the top two leaves and buds of a shrub. A large amount of stems, older leaves and tea wastes from tea factories is not produced. For this reason, study to separation polyphenols from these materials plays an important role in science, society and economy. Polyphenols can be extracted from green tea leaves by using hot water and organic solvents. In the method of using hot water, green tea quality deteriorates and catechins are destroyed due to the heat applied. Therefore, we attempted to increase the amount of polyphenols in extracts with using ultrasonic irradiation at low temperature. This work has an aim to investigate the influent process parameters such as extraction time, stirring speed and the rate of raw material/solvent on efficiency of the extraction of polyphenols and antioxidant properties obtained extracts. The ultrasonic-assisted extraction was conducted at room temperature, ultrasound frequency (25 kHz) using water solvent. Extracts were analysed for total phenols content (TPC) by the Lowenthal method. The antioxidant properties have been determined by DPPH free radical scavenging effect, The results of the work are the basis to determine of the optimal technological factors by employing desirability methodology with experimental order of Box-Behnken design and to scale up for designed industrial extraction system that can be applied in tea plants for the production of tea polyphenols from tea wastes.